2021
DOI: 10.1007/s11136-021-02990-3
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic growth and well-being among people living with HIV: A systematic review and meta-analysis in recognition of 40 years of HIV/AIDS

Abstract: Objectives This systematic review and meta-analysis aimed to synthesize, analyze, and critically review existing studies on the relationship between posttraumatic growth (PTG) and psychological well-being (operationalized either via positive or negative well-being indicators) among people living with HIV (PLWH). We also investigated whether this association varies as a function of socio-demographic, clinical characteristics, and study publication year. Method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 91 publications
4
16
0
2
Order By: Relevance
“…Furthermore, data were obtained from self-reported questionnaires and thus researchers may need to consider social desirability and recall bias. Future studies that replace retrospective, self-reported measures (including PTG) may be beneficial (Pięta & Rzeszutek, 2022). In addition, the current study did not include possible assessment tools that could be important to further explain the role of PTG (e.g., emotional distress, rumination).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data were obtained from self-reported questionnaires and thus researchers may need to consider social desirability and recall bias. Future studies that replace retrospective, self-reported measures (including PTG) may be beneficial (Pięta & Rzeszutek, 2022). In addition, the current study did not include possible assessment tools that could be important to further explain the role of PTG (e.g., emotional distress, rumination).…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerable clinical populations are subjected to dynamic stress circumstances, such as HIV/AIDS stigma, which should be particularly monitored in these patients' daily lives [32]. A particularly interesting question is whether daily uctuations in PLWH's positive and negative well-being are associated with their baseline levels of various stable personal characteristics [33,34]. Therefore, in the current research, we focused on assessing the role of psychological resilience in PLWH's daily lives.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the vast philosophical background for that concept and the numerous theoretical models that emerged over the years, the PTG research area still needs to overcome several important challenges [ 3 , 4 ]. Recent systematic reviews and meta-analyses [ 5 8 ] call for advancements in PTG study designs, including the need for more widespread longitudinal measures of PTG. To this date, very few longitudinal PTG studies have been conducted, and most of these ignore the construct of posttraumatic depreciation (PTD)—defined as reduced of psychological adjustment, impaired cognitive functioning, and low emotional awareness—enabling a parallel measurement of negative changes co-occurring with domains of PTG [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on PTG among PLWH is full of inconsistent results regarding its association with sociodemographic data or HIV-related medical variables [ 19 , 20 ], particularly the time since HIV diagnosis [ 18 , 21 , 22 ]. Also, most studies identify higher PTG levels in women living with HIV, at least in the Western context, and the relationships between PTG and ethnicity, age, and sexual orientation vary depending on the context of a given study [ 8 ]. Moreover, HIV-related psychological distress can be characterized by complex etiology and dynamics, particularly when enhanced by social factors, such as HIV/AIDS stigma [ 8 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation